The Vaporization Threshold: Hypervelocity Impacts of Ice Grains into a Titanium Cassini Spacecraft Instrument Chamber. (2015) - Walker, James D.; Chocron, Sidney; Waite, J. Hunter; Brockwell, Timothy
Abstract: The Cassini spacecraft, currently in orbit around Saturn, has an Ion and Neutral Mass Spectrometer (INMS) on board as part of the scientific payload. There have been some unexpected readings of the instrument in flybys of the moon Enceladus. In relative encounter velocity, these flybys range from 7 to 18 km/s, and it has been suggested that ice grain impacts in the instrument could have a velocity-dependent response that influences the materials that the instrument records. To explore the physics of the impacts, computations were performed with CTH. Small ice grains (1 micron across) were impacted into a titanium alloy at a range of speeds of interest. Results are that the formation of a titanium vapor plume begins at impact velocities of 16 km/s. The transition to the formation of vapor of target material is fairly sharp. We explore the transition to determine the influence of ice grain geometry on the vapor formation transition. Efforts have been made to quantify the titanium vapor and titanium solid and liquid ejecta at various impact speeds, as all of these may influence chemistry in the instrument's antechamber and thus affect what ions or molecules are seen by the INMS.